Temperature and composition of the Earth's core - Alfè, D.; Gillan, M. J.; Price, G. D. (Contemporary physics, 2007)
The Earth's core is a ball of swirling hot metal at the centre of our planet, with a radius roughly one half of the Earth's radius. It is formed by two parts: a solid inner core, with a radius of 1221 km, surrounded by a shell of liquid which extends up to 3480 km from the centre. It is widely believe that the Earth's core is mainly formed by iron, or iron with up to 5 - 10% of nickel. It is also known that the core must contain a significant fraction of light impurities, in the region of 2 - 3% in the solid and 6 - 7% in the liquid. The nature of these light impurities is unknown. The temperature of the core is also inaccessible to direct probing. Here we present a theoretical study on the temperature and the composition of the Earth's core. The investigation is based on the application of the implementation of quantum mechanics known as density functional theory. We shall show that these techniques are very accurate at predicting the properties of iron, and therefore can be usefully used to study the properties of the core. We show that by combining these techniques with direct observations it is possible to predict the temperature of the core, in particular the temperature at the boundary between the solid and the liquid core (the ICB), and put constraints on its composition. The result of this study is that the temperature of the ICB is probably in the region of 5400 - 5700 K and that the outer core contains a significant fraction (8 - 13%) of oxygen. As the Earth cools down the solid core grows and expels oxygen in the liquid. Since oxygen is lighter than iron it rises in the liquid, and its gravitational energy is available to drive the convective motions in the liquid core that are responsible for the generation of the Earth's magnetic field.